MAKNA KEMATIAN DAN MALAIKAT MAUT DRAMA KOREA "TOMORROW": RESEPSI PENONTON BERDASARKAN LIMA AGAMA BERBEDA - Miranda Amelia Novita Sari; Muhamad Husni Mubarok (An-Nida : Jurnal Komunikasi Islam, 2024)
"Tomorrow (2022)" is an intriguing topics of Korean drama series that explores themes of Death and the Grim Reaper, offering a new perspective compared to conventional Indonesian views. This study aims to examine how viewers from diverse cultural and religious backgrounds interpret these themes in the series. Using Stuart Hall's reception analysis framework and a descriptive qualitative methodology, the study focuses on five residents of Bekasi, representing Islam, Christianity, Catholicism, Hinduism, and Buddhism. Data were collected through interviews and scene reviews as part of a documentation analysis process. The findings reveal that viewers’ interpretations of Death and the Grim Reaper are influenced by their religious and cultural backgrounds. Hindu informants generally adopted a dominant-hegemonic interpretation, while Christian informants took an oppositional stance. Informants from Islamic, Catholic, and Buddhist backgrounds showed a negotiation stance. These differences reflect the ideological influences of their respective religions. Despite these differentiatons, all informants agree on the series' dominant-hegemonic portrayal, recognizing "Tomorrow (2022)" as presenting a unique, engaging, and emotionally resonant narrative.